TSLPR deficiency attenuates AHR independently of eosinophilia and mucus secretion in a chronic HDM mouse model of allergic asthma - Latifa Koussih; Sina Taefehshokr; Lianyu Shan; Sujata Basu; Andrew Halayko; Bouchaib Lamkhioued; Abdelilah S. Gounni (PLoS ONE, 2025)
Background Asthma is marked by chronic airway inflammation, immune dysregulation, and airway remodeling. While TSLP is known to influence allergic diseases like asthma, the role of TSLPR in airway remodeling is not well-defined. Methods Using TSLPR-deficient (TSLPR -/- ) mice in a chronic HDM asthma model, we assessed lung function, inflammatory cell infiltration, cytokine levels, and antibody production in serum and lung tissues. Airway remodeling was evaluated by examining mucus production, goblet cell metaplasia, and collagen deposition. Results TSLPR -/- mice showed lower airway resistance, tissue resistance, and tissue elastance compared to wild-type mice after chronic HDM exposure. TSLPR -/- mice also had reduced HDM-specific IgE levels and decreased IL-4, IL-13, and IFN-γ in BALF. However, airway and lung inflammation, including inflammatory cell counts and eosinophil infiltration, were similar between TSLPR -/- and WT mice. Collagen deposition, mucus production, and goblet cell changes were also comparable. Conclusion TSLPR deficiency reduced airway hyperresponsiveness but did not significantly impact lung eosinophil and neutrophil counts or mucus and collagen production in a chronic HDM asthma model, highlighting the complex role of TSLP and TSLPR in severe asthma.